Perawatan Topikal Berbasis Minyak pada Pasien Pruritus Uremik dengan Gagal Ginjal Kronis - Philipus, Vitta Margareth; Yetti, Krisna; Maria, Riri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this study was to look at oil-based topical treatments that are effective in reducing and reducing the scale of uremic pruritus in patients with chronic kidney failure. The research method used in writing this systematic review was a literature search conducted through the Pubmed, Proquest, Science direct, Scopus databases with articles selected from 2010-2022. The results of this study showed a significant reduction in the scale of uremic pruritus in chronic kidney failure patients within 1-4 weeks of oil-based topical treatment. In conclusion, oil-based topical treatments are effective in reducing complaints of itching and pruritus in chronic kidney failure patients so that they can be used in nursing treatment. Key Word: Chronic Renal Failure; Oil Based Treatment ; Uremic Pruritus